On Ng^#- Contra Continuous Functions in Neutrosophic Topological Space - Pious Missier S, Babisha Julit R L, (Design Engineering, 2022)
In this article, we introduce a new concept of Neutrosophic continuous functions called Neutrosophic  contra continuous functions and study their properties in Neutrosophic topological spaces.